Tuberculous Spondylitis: A Report of Different Clinical Scenarios and Literature Update - Catarina Lacerda; Rita Linhas; Raquel Duarte (Case Reports in Medicine)
Tuberculosis is still one of the most important health problems in the world. In developed countries, the proportion of extrapulmonary tuberculosis cases is increasing. Nowadays tuberculous spondylitis, also known as Pott disease, is a rare clinical condition but can cause severe vertebral and neurological sequelae that can be prevented with an early correct diagnosis. The aim of this paper is to increase awareness of tuberculous spondylitis in modern times, describing three different cases and discussing its best diagnostic and therapeutic approach based on the current literature.